Enforcement of Human Rights for Comparative Child Protection Positive Law and Islamic Law - Ratih Agustin Wulandari; Rila Ananda Putri; Izzati Afta Rizki; Aji Tomi Rahmawan; Sri Wahyuni; Muhammad Ihsan (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This journal aims to find out and understand how Islamic law views child protection. The type of research conducted by the authors is descriptive analytical juridical research. Based on the results of this research, it can be concluded how the protection of human rights for children in the perspective of positive law, in Indonesia has been stipulated Law of the Republic of Indonesia No. 39 of 1999 concerning Human Rights which includes children's rights, the implementation of obligations and responsibilities of parents, families, communities, government and the state to provide child protection as a juridical basis for the implementation and responsibilities. Legal protection is all efforts made consciously by everyone as well as government and private institutions that aim to seek security, control and fulfillment of welfare in accordance with existing human rights as stipulated in RI Law No. 39 of 1999 concerning Human Rights. However, the protection of children from all its aspects turns out to require a legal umbrella to create the best life for children who are expected to be the nation's successors who have the potential, are tough, have nationalism imbued with morality and a strong will to maintain the unity and integrity of the nation and state. The legal umbrella in question is RI Law No. 23 of 2002 concerning Child Protection. Article 64 paragraph (2) of the Child Protection Act basically contains all the government's efforts to protect children who are victims of criminal acts. Views of Islamic Law on Child Protection, in Islamic law acts of violence against children are strictly prohibited, because this is a violation of children's rights, because it is not in accordance with human values and religious teachings. In Islamic law, the rights of a child are protected from the time they are born in the womb until they are 18 years old or until they are married. As explained in Q.S Al-Isra (17) verse (70) which means: "And indeed we have glorified the children of Adam, we carried them on land and at sea, we gave sustenance and good things, and we gave them more them with perfect superiority over most of the creatures we have created.